Underage Marriage Review Post Latest Marriage Law - Abdjul, Mohammad Fajar; Kasim, Nur Mohamad; Ismail, Dian Ekawaty (Damhil Law Journal, 2023)
The purpose of this study is to find out about underage marriages after the enactment of the latest marriage law and see how effective the enforcement of the law is and what efforts have been made by the Office of religious affairs against the latest law, which discusses the existence of underage marriages. The research method used is normative, with the statute and contextual approaches. The results of the study show that underage marriages after the entry into force of Law number 16 of 2019 are allowed on the condition that they request a letter of dispensation and are accompanied by urgent reasons and also include supporting evidence and the effectiveness of the latest marriage law in Pohuwato Regency it can be considered ineffective and requires in-depth evaluation because of the high number of underage marriages. Because of this, the Office Of Religious Affairs of Marisa district continues to conduct outreach related to the enforcement of marriage under the law, as regulated in the latest marriage regulations. The government is expected to revise law no. Married even though he is underage, not only in Article 7 paragraph (2), which says the parties' parents can ask the court for dispensation with urgent reasons accompanied by evidence.